2018
DOI: 10.1007/s13595-018-0775-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of soil conditions and light availability on natural regeneration of Norway spruce Picea abies (L.) H. Karst. in low-elevation mountain forests

Abstract: & Key message Natural regeneration of P. abies (L.) H. Karst. may reach high densities in lower mountain elevations. The highest densities were found in sites with moderate light availability, with low pH, and not near the riverbank. However, age-height classes differed in the predicted magnitude of response, but were consistent in response directions. Mosses and understory species typical of coniferous forests were positively correlated with regeneration density. & Context Norway spruce Picea abies (L.) H. Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Furthermore, the positive effect of drought appears to prevent seedlings from a water surplus occurring on clay soil. In addition, balsam fir seedlings occurred mostly on a particular substrate such as woody mounds and thin moss cover [37], known to have a high water capacity, which may explain the absence of the PP_MA effect and the positive effect of drought on seedling abundance [38,39].…”
Section: Anomaly Of Balsam Fir Seedling Abundance (Normal Log Of the ...mentioning
confidence: 99%
“…Furthermore, the positive effect of drought appears to prevent seedlings from a water surplus occurring on clay soil. In addition, balsam fir seedlings occurred mostly on a particular substrate such as woody mounds and thin moss cover [37], known to have a high water capacity, which may explain the absence of the PP_MA effect and the positive effect of drought on seedling abundance [38,39].…”
Section: Anomaly Of Balsam Fir Seedling Abundance (Normal Log Of the ...mentioning
confidence: 99%
“…Riparian forests are characterized by high productivity and biodiversity, play the role of refugia for plants and serve as ecological corridors for populations (Mazal et al, 2022; Pielech et al, 2017; Wierzcholska et al, 2018). Among various types of riparian forests, the narrow habitats formed near springs have received more attention recently due to the maintenance of biodiversity and catchment integrity (Dyderski et al, 2018; González et al, 2017; Naiman et al, 1993; Pielech et al, 2017, 2018; Wierzcholska et al, 2018). In Europe, these valuable habitats, with native broadleaved or mixed forests were transformed for forestry purposes by introducing monocultures of coniferous tree species, which made them very fragmented and modified ecosystems (Bałazy, 2020; Bałazy et al, 2019; Klisz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, our knowledge on transformation of such ecosystems and its consequences for soil fauna is still scarce. Studies conducted in the Sudety Mountains indicated that introduction of Norway spruce (Picea abies) in the place of natural streamside forests changed light conditions, litter type and thickness, and caused acidification (Dyderski et al, 2018;Pielech et al, 2018;Wierzcholska et al, 2018), thus affecting the main environmental factors for soil fauna (Kamczyc et al, 2018;Urbanowski et al, 2018Urbanowski et al, , 2021Woźniak et al, 2022). Information on how environmental parameters vary and impact soil diversity along a distance gradient from the stream into forest, especially on lower mountain elevations in narrow riparian forests, is still scarce.…”
mentioning
confidence: 99%
“…Scientists have demonstrated that post bark beetle outbreaks, nonintervention management is optimal for ecosystem recovery in mountain spruce stands. Benefits include nutrient recycling, preventing mineralization of the soil and the providing of shade, humidity, and cooling favoring natural regrowth (e.g., Bače et al, 2012; Bernes et al, 2015; Dyderski et al, 2018). Logging diminishes biodiversity and limits natural regeneration (Bässler & Müller, 2010; Lehnert et al, 2013; Lindenmayer et al, 2004; Müller et al, 2007, 2008, 2010; Nováková & Edwards‐Jonášová, 2015; Thorn et al, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%